PENGARUH KOMPETENSI PEGAWAI TERHADAP KUALITAS PELAYANAN (STUDI KASUS DI KANTOR KECAMATAN KIARACONDONG KOTA BANDUNG) - Iwan Ardiansyah Ardiansyah (KarismaPro, 2021)
Based on the results of the assessment conducted by researchers at the District Office Kiaracondong Bandung, researchers found the problem was the poor quality of public services. The method used in this research is quantitative research methods through a descriptive approach. The number of samples of the community as listed is a sample of the number of members of a population of 150 members. The survey results revealed that the correlation between employee competence with the quality of public services. The large correlation coefficient is 0.928 (R). R in the correlation, or correlation between two or more independent variables on the dependent variable showed modest correlations. Effect of competency to service quality Kiaracondong subdistrict is high enough influential category of 86.1% this proves that the competence of the employees has a positive and significant impact on the quality of public services, while the remaining 23, 9% is the influence of other variables not examined in this study. Kata kunci: Kompetensi, Kualitas Pelayanan, Pegawai Negeri Sipil